Changes in Lipids in Granulomatosis with Polyangiitis Relates to Glucocorticoids and History of Hypertension - Marialuisa Sveva Marozzi; Antonio Vacca; Vanessa Desantis; Teresa Panebianco; Cristiana Catena; Gabriele Brosolo; Silvia Noviello; Anna Cirulli; Antonio Giovanni Solimando; Leonardo Alberto Sechi; Sebastiano Cicco; Roberto Ria (Metabolites, 2023)
Granulomatosis with polyangiitis (GPA) is an ANCA-associated small-vessel vasculitis. Vessel wall inflammation induces multiple vascular damages, leading to accelerated atherosclerosis. Metabolic profile and cardiovascular risk are somewhat understood in GPA patients. Cardiovascular atherosclerotic disease (ASCVD) may represent a risk for outcomes. Our purpose is to evaluate ASCVD risk in GPA patients. Thirty-six patients received GPA diagnosis (T0) and were evaluated after 1 (T1) and 2 (T2) years follow-up. All patients were treated with high-dose glucocorticoid, one-year tapered, along with immunosuppressants. Total cholesterol significantly increased in T1 vs. T0 and T2. LDL exhibited the same trend, while triglycerides increased in both T1 and T2 vs. T0. No difference was found in HDL. A significant hsCRP decrease was detected at T1 and T2 vs. T0, but not between T2 and T1. Moreover, we found a significant reduction in ESR at T2 compared with T1 and T0 and at T1 compared to T0. Hypertensive patients presented a pronounced increase in lipids, while inflammation reduced slowly compared to normotensives. Our data suggest that the increase in cholesterol and LDL in T1 is a consequence of glucocorticoids. These data can be useful in the evaluation of both CV diseases and lipid metabolism, which are closely related to vessel inflammation.